answersLogoWhite

0


Best Answer

6x - 3y = 6

y= 2x + 5 replace 2x + 5 for y into the first equation

6x - 3y = 6

6x - 3(2x + 5) = 6

6x - 6x - 15 = 6

0 - 15 = 6

-15 = 6 False

So the system has no solution.

User Avatar

Wiki User

βˆ™ 2010-12-04 16:07:44
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

➑️
See all cards
3.75
β˜†β˜…β˜†β˜…β˜†β˜…β˜†β˜…β˜†β˜…
859 Reviews

Add your answer:

Earn +20 pts
Q: What is the answer for 6x-3y equals 6 y equals 2x plus 5?
Write your answer...
Submit
Still have questions?
magnify glass
imp
People also asked